Supplementation of Sambiloto (Andrographis paniculata) Leaf Flour through Broiler Drinking Water against Antibody Titers of Newcastle Disease, Avian Influenza, and Infectious Bursal Disease - Widowati, Mia; Hardiyanti, Cici; Nisak, Rohmatin; Sirat, Muhammad Mirandy Pratama; Ermawati, Ratna (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2022)
The aims of this study were 1) to determine the effect of Sambiloto(Andrographis paniculata)leaf flour supplementation to increase the antibody titer for Newcastle Disease, Avian Influenza, Infectious Bursal Disease; and 2) to determine the best dose of Sambiloto leaf flour supplementation to increase the three antibody titers. The research was carried out in the broiler cage unit of the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung using a completely randomized design experiment with 5 treatments 5 replications and each replication 5 broilers Cobb CP 707 strain, a total of 125 broilers. All broilers were treated with ND, AI, IBD vaccination. Five treatments with different doses, namely drinking water without supplementation with Sambiloto leaf flour (P0); drinking water with Sambiloto leaf flour 3 mg/kg BW (P1); 6 mg/kg BW (P2); 12 mg/kg BW (P3); 24 mg/kg BW (P4). Broiler blood serum aged 26 days was obtained from the brachial vein using a 3-mL disposable syringe. Testing for ND and AI antibody titers with HI test and IBD antibody titer with indirect ELISA test at Vaksindo Agri Lab Laboratory. Data analysis with one-way analysis of variance with Tukey's further test using SPSS 24 software. The results showed that the supplementation of Sambiloto leaf flour in broiler drinking water had no significant effect (P>0.05) on ND and AI antibody titers, while on antibody titers. IBD had a significant effect (Pâ‰¤0.05). The conclusions of this study were 1) the supplementation of Sambiloto leaf flour in broiler drinking water was able to increase the Infectious Bursal Disease antibody titer; and 2) the best dose of Sambiloto leaf flour supplementation in broiler drinking water is 12 mg/kg broiler body weight.